Energy efficiency and carbon savings via a body grid - Jiahe Xu; Xuan Zhang; Daniel M. Kammen; Jiahao Wang; Daimeng Li; Chongbo Sun; Qinglai Guo; Le Xie; Ming Cheng; Shengyu Tao; Hongbin Sun (Communications Engineering, 2025)
Abstract The climate crisis necessitates decarbonization solutions that transform energy systems across all scales. While attention today focuses on utility-scale power systems, mini-or metro-scale grids, and at end-use device efficiency, the individual user scale remains underexplored. Just as with energy efficiency innovations tailored to micro-environments, body-scale energy savings offer new opportunities alongside technological and behavioral challenges. Here we propose a technique and a suite of potential innovations focused on the “body grid” in which devices, circuits, information network, human body and the environment interact within a universal framework to achieve energy savings, new functionality, and improved comfort. We present and test a prototype body grid supporting inter-device synergy and cooperation with external energy systems indoors and outdoors. This system yields substantial energy and economic savings, enhances personal control and comfort, and enables potential energy market participation. Simulation results demonstrate global energy savings of up to 50% for space cooling and heating.